Analisis Pengaruh Variasi Sudut Wedge Pada Treatment Planning System Kasus Kanker Laring - Eunike Winda Ayusari; Taat Guswantoro (Inovasi Kesehatan Global, 2024)
Treatment Planning System (TPS) is a computerized radiation therapy treatment plan using special software with the aim of maximizing the dose to the target (cancer) and minimizing the dose to the surrounding normal tissue. One way to minimize radiation dose to healthy tissue is to create a homogeneous distribution of radiation dose in areas with uneven surfaces such as the neck by utilizing a wedge filter. Researchers compared the results of TPS with varying wedge angles ranging from 15o, 30o, 45o, and 60o and assessed the effectiveness against cancer based on the isodose curve, in cases of laryngeal cancer. From the results of this comparison, the use of a 15o wedge is considered less effective because the radiation dose distribution does not cover the entire larynx. The use of a 30o wedge is considered effective because the maximum radiation dose distribution covers the entire larynx. The use of a 45o wedge is considered ineffective because the maximum radiation dose distribution is found in almost all organs in the neck. The use of a 60o wedge is considered ineffective because the dose distribution in the neck has a radiation dose of above 110% or even 125%. From the results of the comparison of wedge angle variations, an angle of 30o is considered the most effective so that it can be used for implementing the Treatment Planning System in the field.